Association of early life health conditions, nutritional status, and feeding practices with caries prevalence in preschool children - Caroline Harmatiuk (RSBO Revista Sul-Brasileira de Odontologia, 2016)
Objective: This study aimed to determine whether health conditions in the first year of life, nutritional status and dietary habits throughout life are related to the prevalence of early childhood caries (ECC). Material and methods: Sample consisted of 338 children from public schools. The prevalence of dental caries was assessed by dmf-t index. An anthropometric analysis was conducted for identification of nutritional risk. Data were analyzed using Chi-square and Poisson regression analysis, considering the dependent variables: a) presence of ECC (dmft ≥ 1); b) presence of severe ECC (dmft ≥ 6). Results: It was observed that 64% of the children exhibited ECC (mean dmft 2.97) and 23% suffer from severe ECC (mean dmft 8.2). 28 (11%) were at nutritional risk and more than 30% consumed sweets one or more times a day. It was observed that 8% showed low birth weight, 9% used antibiotics frequently in the first year of life and 67% maintained the habit of nocturnal bottle/breast-feeding after this period. Nocturnal feeding for prolonged time, frequent use of antibiotics and nutritional risk were associated with higher prevalence and severity of caries in the multivariate analysis. Conclusion: These results reinforce the relationship between early life events, nutritional status, and dental caries in primary teeth.